Column repair and strengthening using RC jacketing: a brief state-of-the-art review - Habib, Ahed; Yildirim, Umut; Eren, Ozgur (Springer International Publishing Ag, 2020)
Seismic retrofitting and/or the strengthening of RC columns has been a popular area of research for decades. Currently, reinforced concrete jacketing is considered as the most common technique for repairing and strengthening of deficient and/or damaged RC columns. In general, this technique is a practical solution to recover and improve the load-carrying capacity and stiffness of reinforced concrete columns in earthquake-prone countries. It is a simple method that can be applied to any column cross section for rehabilitating structural elements by encasing the old member in a stiff jacket. The importance of this approach comes from its ability to improve the load-carrying capacity, strength, and stiffness of any column section significantly without the need for experienced labor or complicated installations process. This paper summarizes and compares general conclusions of recent investigations on columns retrofitting using reinforced concrete jacketing. As a part of this study, experimental, analytical, and numerical studies were reviewed and their findings were collected and discussed.
Keywords: Reinforced concrete jacketing; Concrete column; Strengthening; Repairing